Effects of integration time on rain rate distribution for microwave link design - Momin, Mullah (Springer, 2022)
Rain fade is the main constraint for microwave propagation at higher frequencies. To design microwave link, it contributes significantly specially in tropical region. All rain attenuation prediction models require rain intensity data based on 1-min integration time. Rain intensity data was collected at International Islamic University Malaysia with 10-s integration time for one year period. The measured intensity was converted to 20-s, 30-s, 1-min and 2-min integration time to investigate the effects of integration time on rain rate distribution prediction as well as rain attenuation prediction models and the results are presented on this paper.